The effects of melatonin in the treatment of acute brachial plexus compression injury in rats - Li, Xigong; Fu, Jing; Zhou, Haiying; Dong, Yanzhao; Alhaskawi, Ahmad; Wang, Zewei; Lai, Jingtian; Yao, Chengjun; Ezzi, Sohaib Hasan Abdullah; Kota, Vishnu Goutham; Abdulla, Mohamed Hasan Abdulla Hasan; Guan, Ming; et al. (Frontiers in Neurology, 2023)
Introduction Brachial plexus injury (BPI) is one of the most destructive peripheral nerve injuries and there is still a lack of effective treatment. Methods This study was conducted to evaluate the effects of melatonin in the treatment of acute brachial plexus compression injury in rats using histopathological, histomorphometric, immunohistochemical and electrophysiological methods. Forty-eight adult male Sprague Dawley rats were randomly allocated into three groups: sham, melatonin and vehicle groups. The brachial plexus compression injury model was performed by a vascular clamp. Melatonin group received intraperitoneal injection of melatonin at doses of 10 mg/kg for 21 days after crush injury. The conduction velocity and amplitude of compound muscle action potential (CAMP) in the regenerated nerve, and nerve histomorphometry, as well as levels of myelin protein zero (P0) protein of the crush region were assessed. Results Compared with the vehicle group, the melatonin group which reported significant increased CMAP conduction velocity and amplitude also showed thicker myelin sheath and lower levels of P0 protein. Discussion Our results suggest that melatonin effectively promotes nerve regeneration and improves the function of damaged nerves. Melatonin treatment is a promising strategy for the treatment of acute brachial plexus compression injury.